2009
DOI: 10.1525/mp.2009.26.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Emotion in Motion: Investigating the Time-Course of Emotional Judgments of Musical Stimuli

Abstract: MUSIC ELICITS PROFOUND EMOTIONS; HOWEVER, THE time-course of these emotional responses during listening sessions is unclear. We investigated the length of time required for participants to initiate emotional responses ("integration time") to 138 musical samples from a variety of genres by monitoring their real-time continuous ratings of emotional content and arousal level of the musical excerpts (made using a joystick). On average, participants required 8.31 s (SEM = 0.10) of music before initiating emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
3
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 39 publications
6
49
3
9
Order By: Relevance
“…We infer that most players are unable to instantaneously judge the mood of a clip at its onset. This is consistent with other research by Bachorik, which concluded that most music listeners require about 8 seconds to judge the mood of a song [9].…”
Section: Analysis Of Datasupporting
confidence: 93%
“…We infer that most players are unable to instantaneously judge the mood of a clip at its onset. This is consistent with other research by Bachorik, which concluded that most music listeners require about 8 seconds to judge the mood of a song [9].…”
Section: Analysis Of Datasupporting
confidence: 93%
“…Although formal training in music is unlikely to matter much (Adachi et al, 2004;Bachorik et al, 2009;Bigand, Vieillard, Madurell, Marozeau, & Dacquet, 2006), listening experience would likely play a role, with accuracy improving with increased exposure to music. The association between accuracy and liking suggests that greater exposure during childhood may lead to more adult-like preferences, at least until early adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Schubert (2013) describes the time interval during which the accuracy of a participant's rating of a musical stimulus are confounded by the time needed to orient to the music and the mechanics of the rating interface, called the initial orientation time. Another study described this period on a similar interface as the integration time, reporting an average of 8.3 s before participants' ratings settled in a region of the rating range (Bachorik et al, 2009). Some of the largest rating changes can occur in this interval, and this is expected to compromise average rating time series.…”
Section: Coherence Measures Between Collections Of Responsesmentioning
confidence: 99%